Yacimientos uraníferos. Los minerales de uranio y de torio - Linares, Enrique; Latorre, Carlos O. (Comisión Nacional de Energía Atómica; Argentina, 1970)
Fil: Linares, Enrique Comisión Nacional de Energía Atómica; Argentina